FDI and income inequality: Evidence from Latin American economies - Dierk Herzer; Philipp Hühne; Peter Nunnenkamp (Kiel Institute for the World Economy (IfW), 2012)
We analyze whether foreign direct investment (FDI) has contributed to the typically wide income gaps in five Latin American host countries. We perform country-specific and panel cointegration techniques to assess the long-run impact of inward FDI stocks on income inequality among households in Bolivia, Chile, Colombia, Mexico and Uruguay. The panel cointegration analysis reveals a significant and positive effect on income inequality. Furthermore, FDI contributed to widening income gaps in all individual sample countries, except for Uruguay. Our findings are robust to the choice of different estimation methods. There is no evidence for reverse causality.
Keywords: F21; D31; 330; FDI; income inequality; cointegration techniques; Latin America